Only Time Will Tell: A Theory of Deferred Compensation. (3rd August 2020) - Hoffmann, Florian; Inderst, Roman; Opp, Marcus
Abstract: This article characterizes optimal compensation contracts in principal-agent settings in which the consequences of the agent's action are only observed over time. The optimal timing of pay trades off the costs of deferred compensation arising from the agent's relative impatience and potential consumption smoothing needs against the benefit of exploiting additional informative signals. By capturing this information benefit of deferral in terms of the likelihood ratio dynamics, our characterization covers general signal processes in a unified setting. With bilateral risk neutrality and agent limited liability, optimal contracts are high-powered and stipulate at most two payout dates. If the agent is additionally risk-averse, payouts are contingent on performance exceeding a hurdle that is increasing over time. We obtain clear-cut predictions on how the duration of optimal compensation depends on the nature of information arrival as well as agent characteristics and derive implications for the maturity structure of securities in financial contracting settings.